Aging of Dissolved Copper and Copper‐based Nanoparticles in Five Different Soils: Short‐term Kinetics vs. Long‐term Fate. Issue 6 (1st November 2017) - Sekine, Ryo; Marzouk, Ezzat R.; Khaksar, Maryam; Scheckel, Kirk G.; Stegemeier, John P.; Lowry, Gregory V.; Donner, Erica; Lombi, Enzo
Abstract : With the growing availability and use of copper‐based nanomaterials (Cu‐NMs), there is increasing concern regarding their release and potential impact on the environment. In this study, the short‐term (≤5 d) aging profile and the long‐term (135 d) speciation of dissolved Cu, copper oxide, and copper sulfide nanoparticles (CuO‐NPs and CuS‐NPs) were investigated in five different soils using X‐ray absorption spectroscopy. Soil pH was found to strongly influence the short‐term chemistry of the Cu‐NMs added at 100 mg kg −1 above background. Low pH soils promoted rapid dissolution of CuO‐NPs that effectively aligned their behavior to that of dissolved Cu within 3 d. In higher pH soils, CuO‐NPs persisted longer due to slower dissolution in the soil and resulted in contrasting short‐term speciation compared with dissolved Cu, which formed copper hydroxides and carbonates that were reflective of the soil chemistry. Organic matter appeared to slow the dissolution process, but in the long term, the speciation of Cu added as dissolved Cu, CuO‐NPs, and CuS‐NPs were found to be same for each soil. The results imply that, in the short term, Cu‐NMs may exhibit unique behavior in alkaline soils compared with their conventional forms (e.g., in the event of an adverse leaching event), but in the long term (≥135 d), their fates are dictated by the soil properties, are independent of the initial Cu form, and are likely to present minimal risk of nanospecific Cu‐NM impact in the soil environment for the concentration studied here. Core Ideas: Short‐term reactions of Cu are form (dissolved or nanoparticle) and soil chemistry dependent. In low pH soils, CuO‐NPs dissolved rapidly and behaved similarly to dissolved Cu. CuO‐NPs persisted longer in alkaline soils and soils with high organic matter content. In the long term, Cu, CuO‐NPs, and CuS‐NPs transform into Cu bound to FeO(OH) or NOM. Chemical fate of Cu added to soils is largely independent of the original Cu form.